Adaptive frequency-domain equalization and diversity combining for broadband wireless communications. - Clark, M.V.
We introduce a new kind of adaptive equalizer that operates in the spatial-frequency domain and uses either least mean square (LMS) or recursive least squares (RLS) adaptive processing. We simulate the equalizer's performance in an 8-Mb/s quaternary phase-shift keying (QPSK) link over a frequency-selective Rayleigh fading multipath channel with ~3 μs RMS delay spread, corresponding to 60 symbols of dispersion. With the RLS algorithm and two diversity branches, our results show rapid convergence and channel tracking for a range of mobile speeds (up to ~100 mi/h). With a mobile speed of 40 mi/h, for example, the equalizer achieves an average bit error rate (BER) of 10 -4 at a signal-to-noise ratio (SNR) of 15 dB, falling short of optimum linear receiver performance by about 4 dB. Moreover, it requires only ~50 complex operations per detected bit, i.e., ~400 M operations per second, which is close to achievable with state-of-the-art digital signal processing technology. An equivalent time-domain equalizer, if it converged at all, would require orders-of-magnitude more processing
Keywords: BER; LMS; QPSK link; RLS algorithm; SNR; Adaptive frequency-domain equalization; Adaptive processing; Average bit error rate; Broadband wireless communications; Cellular telephony; Channel tracking; Convergence; Delay spread; Digital signal processing technology; Diversity combining; Equalizer performance; Frequency-selective Rayleigh fading multipath channel; Least mean square; Mobile speeds; Optimum linear receiver performance; Quaternary phase-shift keying; Recursive least squares; Signal-to-noise ratio; Spatial-frequency domain; Time-domain equalizer